STRATEGI PEMBELAJARAN BAHASA INGGRIS SEBAGAI BAHASA ASING DALAM MENINGKATKAN KEMAMPUAN BERBAHASA SISWA - Idham Syahputra (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
One of the aspects that determine the success of learning is learning strategies used. Therefore, teachers should be able to select and use the appropiate strategies to the learning objectives that will be achieved. There are saveral strategies in English can be selected and used by the teachers in learning process to improve the learning achievement of students in four skills of English. Teacher is suggested to use variation strategies that can increase the learning experience for students. Varied leaning strategies can increase the learning outcomes and students’ language skills